2006
DOI: 10.1093/hmg/ddl439
|View full text |Cite
|
Sign up to set email alerts
|

Pael receptor induces death of dopaminergic neurons in the substantia nigra via endoplasmic reticulum stress and dopamine toxicity, which is enhanced under condition of parkin inactivation

Abstract: Selective loss of dopaminergic neurons is the final common pathway in Parkinson's disease. Expression of Parkin associated endothelin-receptor like receptor (Pael-R) in mouse brain was achieved by injecting adenoviral vectors carrying a modified neuron-specific promoter and Cre recombinase into the striatum. Upregulation of Pael-R in the substantia nigra pars compacta of mice by retrograde infection induced endoplasmic reticulum (ER) stress leads to death of dopaminergic neurons. The role of ER stress in dopam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
87
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(88 citation statements)
references
References 30 publications
1
87
0
Order By: Relevance
“…GPR37 is a substrate of the parkin ubiquitin-protein ligase, and its insoluble aggregates are found accumulated in brain samples of PD patients. The experimental overexpression of the receptor protein in neuronal cell cultures and in Drosophila and mouse dopaminergic neurons in vivo leads, in absence of parkin, to selective cell death (3)(4)(5)(6). In a previous paper we reported that Gpr37-null mutant mice exhibit a reduction in striatal DA content, specific locomotor deficits, and enhanced sensitivity to amphetamine (8), indicating the functional alteration of the nigrostriatal dopaminergic signaling pathway.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…GPR37 is a substrate of the parkin ubiquitin-protein ligase, and its insoluble aggregates are found accumulated in brain samples of PD patients. The experimental overexpression of the receptor protein in neuronal cell cultures and in Drosophila and mouse dopaminergic neurons in vivo leads, in absence of parkin, to selective cell death (3)(4)(5)(6). In a previous paper we reported that Gpr37-null mutant mice exhibit a reduction in striatal DA content, specific locomotor deficits, and enhanced sensitivity to amphetamine (8), indicating the functional alteration of the nigrostriatal dopaminergic signaling pathway.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, the GPR37 activation by cognate neuropeptide ligands might be critical for modulating DAT expression at the plasma membrane. GPR37 is considered to be involved in the neuropeptide regulation of cell survival during brain development and in the differentiation of glial cells and neurons (3)(4)(5)(6)(7), and it interacts with the morphogenetic head activator neuropeptide and its binding protein SorLA upon expression in transfected culture cells (7). Because the peptide activation of GPR37 would cause the receptor down-regulation by phosphorylation and internalization (28), this could, in turn, result in the increased internalization of DAT and other proteins interacting with GPR37 (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parkin was shown to be transcriptionally regulated by ATF4, thus suggesting that it acts as a ER stress-inducible protein that mediate cytoprotective mechanisms [83] and its subcellular distribution is altered following ER stress [84]. Of interest, Parkin-associated endothelin-receptor like receptor (Pael-R), a target for Parkin-dependent degradation by the proteasome, was shown to induce UPR triggering thus leading to neuronal death, a condition that were worsened by ER chaperone dysfunction [85].…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…Also, neurons of Pael-R transgenic mice were more susceptible to PD related toxins-induced cell death, by a mechanism involving unfolded protein stress response [55]. Furthermore, excessive Pael-R expression in parkin KO mice induced cell death [56]. Pael-R is a homologue to endothelin receptor type B, which has been shown to regulate phospholipase (PLC) activity [43] and subsequently the mobilization of intracellular Ca 2+ and facilitation of Ca 2+ influxes [47].…”
Section: Cell Survival Related Signalingmentioning
confidence: 99%